Psychosocial impacts of the COVID-19 pandemic among settled women: A longitudinal study - Jaqueline Lemos de Oliveira; Janaina Cristina Pasquini de Almeida; Antonio Jose Correa de Pauli; Mara Regina Moitinho; Regina Célia Fiorati; Jacqueline de Souza (Universidade de São Paulo, 2023)
Abstract Objective: to analyze the psychosocial impacts of the COVID-19 pandemic among Brazilian women from rural settlements. Method: this is a quantitative and longitudinal study conducted with 13 settled women. The data were collected between January 2020 and September 2021 using questionnaires on the perception of the social environment (quality of life, social support, self-efficacy), common mental disorder symptoms and sociodemographic aspects. The data were analyzed using descriptive statistics, cluster analysis and variance analysis. Results: intersecting vulnerability conditions were identified that possibly intensified the challenges arising from the pandemic. The Quality of Life physical domain fluctuated differently and inversely according to the mental disorder symptoms. As for the psychological domain, at the end of the segment, an increase over time was identified in the entire sample, as the women's perception was better than before the pandemic. Conclusion: worsening of the participants' physical health deserves to be highlighted and, probably, it can be related to the difficulty accessing health services in this period as well as to the fear of contamination. Despite this, the participants were emotionally resilient throughout the period, including signs of improvement in terms of psychological aspects, suggesting a possible effect of the community organization of the settlement.